Gaps of Workplace English Needs Perceived by Pre-service Medical Record Technicians : Penelitian - Ika Sulis Setianingsih; Risa Arroyyani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study investigates the workplace English needs of pre-service Medical Record and Health Information technicians through a theoretically grounded qualitative needs analysis. The research aims to identify how English is functionally used in professional medical record contexts and how learner perceptions align with institutional demands by drawing on contemporary frameworks in English for Specific Purposes (ESP), English for Medical Purposes (EMP), task-based language teaching, genre-based pedagogy, and communicative competence theory. Data were collected from 90 final-semester students through an open-ended questionnaire, yielding 128 responses that were thematically coded into five skill categories: speaking, reading, writing, listening, and general/abstract use. The findings showed that speaking is perceived by students as the most prominent English skills due to its visibility in interactions with foreign patients, especially in registration and frontline services. However, triangulation with the Indonesian National Work Competency Standards (SKKNI) indicates that reading-intensive tasks, such as diagnostic coding, system navigation, and data validation, establish the cognitive core of medical record work. Writing functions primarily as a structured extension of reading through standardized documentation and reporting, while listening remains underreported despite its embedded role in workplace communication. This discrepancy highlights a persistent gap between perceived communicative prominence and actual operational task frequency. The study emphasizes the necessity of integrating regulatory frameworks and occupational task analysis into EMP curriculum design to ensure pedagogical alignment with workplace realities.